Addition of Macro Nutriens, Micro Nutriens and Garlic Flour to Formulated Fish Feed on Growth Performance of Cantang Grouper (Epinephelus fuscoguttatus x Epinephelus lanceolatus) (Jurnal Intek Akuakultur, 2022)
This research aimed to determine the effect of adding Macro nutriens, Micro nutriens and Garlic Flour to the formulated fish feed on growth performance of the hybrid cantang grouper (Epinephelus fuscoguttatus x Epinephelus lanceolatus). This research was conducted from February to April 2020 in the Madong village, Silver pompano (Tranchinotus blochii) culture group, Tanjung Pinang, Riau Islands Province. Methodology used in this research was an experimental method with a Completely Randomized Design (CRD) consists of 4 treatments and 3 repititions, which the K treatment is : (Formulated fish feed (700g catfish pellets + 300g lemuru fish flour), treatment A: (Formulated fish feed + 5g macro and micro nutriens / kg of feed), treatment B: (Formulated fish feed + 1g of garlic flour), and treatment C: (Formulated fish feed + 5g macro and micro nutriens + 1g of garlic flour /kg of fish feed). Analysis of the data with Analysis of Variance (ANOVA) and Tukey's further tests, showed that the addition of macro nutriens, micro nutriens and garlic flour to the feed had a significant effect on the cantang grouper growth performance. Treatment of 5g macro and micro nutriens + 1g of garlic flour/kg of feed or C treatment was the best treatment, the results obtained in the growth of absolute weight (13.94 Â± 0.19 g) and feed efficiency (35.28 Â± 0.89 %).